A Attitudes toward Feminism in a Patriarchal Muslim Country: The Impact of Religiosity, Background, Gender, Education, and Sect - Yousaf, Muhammad; Murtaza, Insia; Javed, Saba; Khalid, Zonera (Journal of Peace, Development and Communication, 2024)
This study intends to investigate the attitudes toward feminism in a patriarchal Muslim country. The study explores the influence of religiosity, background, gender, education, and sect. The study used a cross-sectional research design vis-à-vis survey method. A survey questionnaire with demographic variables was administered to three religious seminaries and two university students in Lahore to collect data. The sample for the study consisted of 340 respondents. It was found that university and religious seminary students differed regarding their attitudes towards feminism with females being more feminist compared to males. Moreover, background also played a significant role toward feminism. Religious sect also played a significant role regarding the attitudes of students towards feminism. However, age was found to have no influence on the attitudes towards feminism. These findings have implications for creating a harmonious society vis-à-vis implementation of diverse curriculum.